MAKNA â€œCANTIKâ€ DARI SEBUAH BARBIE: ANTARA â€œIKONâ€ GAYA HIDUP DAN KOMODITAS - Aris Saefulloh (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Barbie, a doll that first time exists in America at 1959, has become a lifestyle icon that represents beauty. Barbie act ascultural icon that able to fill a niche that replace religious symbols as cross or saints statue, especially at secular country like America, andEurope countries. As a beauty representation, many women at entire world have imagination and even trying to imitate and follow Barbiestyle. Barbie have created by global capitalist (Barbie industry) as an opportunity to market expansion